2021
DOI: 10.1017/s1047951121003024
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiac echocardiogram findings of severe acute respiratory syndrome coronavirus-2-associated multi-system inflammatory syndrome in children

Abstract: Background: A novel paediatric disease, multi-system inflammatory syndrome in children, has emerged during the 2019 coronavirus disease pandemic. Objectives: To describe the short-term evolution of cardiac complications and associated risk factors in patients with multi-system inflammatory syndrome in children. Methods: Retrospective single-centre study of confirmed multi-system inflammatory syndrome in children treated from 29 March, 2020 to 1 September, 2020. Cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 42 publications
2
31
0
Order By: Relevance
“…Several studies have reported the short-term outcomes of cardiac complications in children with MIS-C. Cardiac complications persisted during firsty and second months at follow-up in two studies [48,49]. Caro-Paton et al [50] showed [52].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the short-term outcomes of cardiac complications in children with MIS-C. Cardiac complications persisted during firsty and second months at follow-up in two studies [48,49]. Caro-Paton et al [50] showed [52].…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of our study include the fact that we limited cardiac complications for comparison to coronary artery abnormalities or decreased systolic function, and did not include valvular regurgitation or pericardial effusion, although in our overall institutional cohort, these findings have been observed to be the most transient and likely to resolve during short-term follow-up. 3…”
Section: Discussionmentioning
confidence: 99%
“…Due to unusual severity, case 12 has been reported previously. 3 To calculate the incidence of myopericarditis associated with mRNA COVID-19 vaccination among Danish adolescents, the number of individuals 12-17 years of age who had received 1 dose of mRNA COVID-19 vaccine from May 15 to August 15, 2021, was attained from the National COVID-19-vaccine Database at the Statens Serum Institut.…”
Section: Methodsmentioning
confidence: 99%
“…The recent emergence of 2019 coronavirus disease (COVID-19) and the similarity between KD and the Multi-System Inflammatory Syndrome in Children (MIS-C) brought to the stage the importance of studying KD globally [ 12 20 ]. Through professional and personal communications among peers in Middle Eastern countries, a growing concern and awareness toward KD was a recurrent theme.…”
Section: Introductionmentioning
confidence: 99%